The Influence of Leadership Motivation on Employee Performance for Development of Human Resources in The Government of Ogan Komering ULU Timur - Gatronado Garaika (eCo-Fin, 2020)
In supporting the progress and development of an organization it is very necessary to be carried out seriously and continuously in all fields and all aspects of life. The availability of quality human resources and have a high work ethic is the main capital of an organization to be aligned with other organizations. Without the individuals of each individual to try to progress without the need to be forced, then an orSuch ganization does not mean anything. In the human resource development and human resource development department of East Ulu Komering, apparently the directives have not been carried out properly so that the performance of employees is not optimal. The problem faced is how the influence of direction on the performance of the budget department employees in the human resource development and human resource development in East Ulu Komering. the purpose of this study was to determine the effect of direction on employee performance in the human resource and human resource development of the East Ulu Komering and useful as a reference for further research on the direction and performance of pegwai.hipotesis proposed, briefing has a positive effect on employee performance in the human resource and human resource development of the East Ulu Komering. data collection and processing using literature and field studies using observations, questionnaires, interviews and documentation. From the results of the discussion obtained the correlation between direction in an effort to improve the performance of employees at the human resources agency and the development of human resources of East Ulu Komering obtained the number r of 0.57. So it can be said that there is a moderate influence between directing on the performance of employees at the human resources agency and the development of human resources in Ogan Komering Ulu Timur.